2022
DOI: 10.4143/crt.2020.1247
|View full text |Cite
|
Sign up to set email alerts
|

Increased Radiosensitivity of Solid Tumors Harboring ATM and BRCA1/2 Mutations

Abstract: Preclinical data indicate that response to radiotherapy (RT) depends on DNA damage repair. In this study, we investigated the role of mutations in genes related to DNA damage repair in treatment outcome after RT. Materials and MethodsPatients with solid tumor who participated in next generation sequencing panel screening using biopsied tumor tissue between October 2013 and February 2019 were reviewed and 97 patients that received RT were included in this study. Best response to RT and the cumulative local recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“… 27 Recently, a study by Kim et al demonstrated that solid tumors harboring BRCA1/2 variations exhibited increased sensitivity to radiotherapy compared to those without these alterations. 9 Our case is consistent with the findings of Kim et al in this regard.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 27 Recently, a study by Kim et al demonstrated that solid tumors harboring BRCA1/2 variations exhibited increased sensitivity to radiotherapy compared to those without these alterations. 9 Our case is consistent with the findings of Kim et al in this regard.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that mutations in DDR genes, including BRCA1/2 , potentially enhance radiosensitivity in patients with diverse solid tumors. 9 However, DDR-gene mutations, as predictive biomarkers for radiotherapy in primary mediastinal YSTs, have not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our patient had almost a 50% reduction in target volume, potentially due to the longer span in overall treatment time. The reduction may have also been associated with his BRCA2 mutation status as there are reports of increased radiosensitivity in normal and tumor cells of BRCA mutation carriers ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 and BRCA2 play a pivotal role in HR, and a higher risk of contralateral breast cancer was described in patients with germline mutation who underwent adjuvant RT after breast surgery [ 47 ]. Kim et al [ 48 ] described a significantly higher objective response and a lower local recurrence rate in patients with BRCA mutation treated with RT and a dramatic and durable response when there was also a concomitant ATM mutation (1-year local recurrence rate at 0% in BRCA + ATM mutated vs. 47.9% in wild type, p = 0.008) without an increased toxicity rate.…”
Section: Genetic Alterations and Non-coding Rna As Predictors Of Radi...mentioning
confidence: 99%